2020
DOI: 10.1002/ps.6021
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal activity of substituted chalcones against Aedes aegypti (Diptera: Culicidae) and non‐target organisms

Abstract: BACKGROUND: The expansion of Aedes aegypti (Diptera: Culicidae) population has increased the number of cases of arboviruses, in part due to the inefficiency and toxicity of the chemical control methods available to control this vector. We synthesized 19 chalcone derivatives and examined their activity against Ae. aegypti larvae in order to select larvicidal compounds that are non-toxic to other organisms. RESULTS: Seven chalcone derivatives (3a, 3e, 3f, 6a, 6c, 6d, and 6f) had lethal concentrations of substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 90 publications
(161 reference statements)
1
11
0
1
Order By: Relevance
“…9−12 Recently, it has been reported that chalcones have been served as novel insecticides to control insect population, such as angular benzofuran chalcones, 13 chemically modified chalcones, 14 the chalcone derivatives kanakugiol, hydroxychalcone and cardamonin, 15 and furan-chalcones. 16 Moreover, the fungistatic and fungicidal effects of chalcones have also been investigated against phytopathogens in greater detail, including geranyl chalcones, 17 chalcone-based strobilurins, 18 dihydrochalcones (mainly phloridzin, sieboldin, trilobatin, and phloretin), 19 vanillin-chalcones, 20 ferrocenyl-chalcones, 21 isobavachalcones, 22 dihydrochromane-chalcones, 23 and isobavachalcones. 24 In contrast, the herbicidal activity of chalcones has been less investigated.…”
Section: ■ Introductionmentioning
confidence: 99%
“…9−12 Recently, it has been reported that chalcones have been served as novel insecticides to control insect population, such as angular benzofuran chalcones, 13 chemically modified chalcones, 14 the chalcone derivatives kanakugiol, hydroxychalcone and cardamonin, 15 and furan-chalcones. 16 Moreover, the fungistatic and fungicidal effects of chalcones have also been investigated against phytopathogens in greater detail, including geranyl chalcones, 17 chalcone-based strobilurins, 18 dihydrochalcones (mainly phloridzin, sieboldin, trilobatin, and phloretin), 19 vanillin-chalcones, 20 ferrocenyl-chalcones, 21 isobavachalcones, 22 dihydrochromane-chalcones, 23 and isobavachalcones. 24 In contrast, the herbicidal activity of chalcones has been less investigated.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The chalcones 4-CL and DMF have been shown to have diverse biological activities and pharmaceutical applications [11][12][13][14][15][16][17][18][19][21][22][23]. However, the toxicogenetic risk information about them is mandatory to ensure their safe use [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, according to Chen et al [17], DMF exhibited cardioprotective and potential anticancer effects in mice thought the activation of pro-autophagic transcription factors. The chalcone 4-CL has presented also others activities, such as antioxidant [18], antiprotozoal [19], antinociceptive [20], anti-inflammatory [18], larvicidal [21,22], osteogenic [23], antiplasmodial activity [24] and no neurotoxic effect [25]. According to Sahin et al [26], chalcone 4-CL can be also considered as good candidate for liver cancer therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…The structurally related chalcones have also been investigated as mosquito larvicides and the compound (E)-3-(4-bromophenyl)-1-(furan-2-yl) prop-2-en-1-one exhibited an LC 50 value of 6.66 mg/L at 24 h against Ae. aegypti larvae [36]. Additionally, 28 compounds, chalcones and some derived products, were synthesized and tested for mosquito larvicidal activity against the third instar larvae of Cx.…”
Section: Calculations Of Molecular Descriptorsmentioning
confidence: 99%